Spatio-temporal dynamics of water resources of Hyderabad Metropolitan Area and its relationship with urbanization. (December 2020) - Nayan, Nakul kumar; Das, Arup; Mukerji, Arjun; Mazumder, Taraknath; Bera, Subhas
Highlights: Changes in urban water spread through analyses of RS imagery compared with land use to identify effects of urbanization on surface water. Geo-statistical cluster analysis of groundwater with land use and development intensity to inspect dynamics of urbanization and groundwater. Conversion of surface waterbodies to residential and public land use – indicating encroachment, insensitivity of governmental agencies. Depletion of groundwater resources, with most significant losses accounted under commercial land use. No significant evidence of groundwater depletion in the fringe areas of the metropolitan region. Abstract: Urbanization brings about changes in land use and land cover (LULC), and intensity of development. Most anthropogenic activity in urban areas are dependent on its water resources. Hence, an investigation of the relationship between urbanization and water resources of an urban area needs to be conducted. As the catchment area of the water resources in an urban area often extends beyond its administrative boundaries, a regional approach is needed for such studies. This study develops a methodology to assess the impact of change in LULC on the water resources of a metropolitan region with Hyderabad as a case example. The image processing and GIS based analyses reveal substantial decrease in the surface water area due to transformation of LULC from waterbodies to other uses. It also exhibits a positive correlation between existing land use mix and change in groundwater level. Spatial clustering analyses revealed that areas with commercial land use exhibit maximum deterioration of groundwater level. Whereas, analyses of the intensity of growth show that areas with midrise and low rise development (peri urban regions) displayed an improvement in groundwater level, but areas within the study area having high rise development (commercial/HIG residential region) show maximum attenuation of groundwater resources.